mꜣʿ ḫrw," before the Fifth Dynasty? - SHAPIRA, GUY (Journal of the American Oriental Society)
This note presents the earliest known attestations of the epithet mAa xrw, "true of voice," dating to the early Third Dynasty. It offers a preliminary discussion of their significance and implications for the study of Maat and the religious history of the Old Kingdom in general.